FEATURES OF EDUCATIONAL PRACTICE IN AGROECOLOGY IN DISTANCE FORMAT - Фінько, Марина; Бережняк, Євгеній (SWorldJournal, 2022)
The paper presents the main methods of research and topics for educational practice in agroecology in distance mode. It is noted that the best way for students to learn the necessary practical materials was their opportunity to watch videos and photos of